Longitudinal assessment of systolic anterior motion of the mitral valve in cats with hypertrophic cardiomyopathy. - Seo J; Novo Matos J; Munday JS; Hunt H; Connolly DJ; Luis Fuentes V (Wiley Periodicals LLC on behalf of American College of Veterinary Internal Medicine, 2024)
BACKGROUND: The proportion of cats with hypertrophic cardiomyopathy (HCM) that lose systolic anterior motion of the mitral valve (SAM) in the long term is unknown. HYPOTHESIS/OBJECTIVES: Cats with HCM will lose SAM in the long term. Loss of SAM will be associated with greater age, longer scan-interval, and altered left ventricular (LV) dimensions. ANIMALS: Sixty unsedated cats with HCM, not receiving beta blockers or pimobendan. METHODS: A retrospective cohort study from 2 referral centers. Cats were eligible if they had been diagnosed with HCM and had a repeat echocardiogram ≥1 year later. Clinical and echocardiographic data of the left heart variables were collected. RESULTS: Thirty-eight cats had SAM at the initial scan. After a median follow-up time of 2.1 years (range: 1.0-5.9), 7 cats had lost SAM (18%) and 5 cats (23%) gained SAM. On follow-up, cats with SAM at the initial scan had a larger left atrium (P = .037), lower left atrial fractional shortening (P = .014), greater LV internal diameter in end-systole (P = .002), and lower LV fractional shortening (P < .001). Four cats with SAM developed congestive heart failure. There were no new cases of congestive heart failure or change in left heart variables in cats without SAM at the initial scan. The gain or loss of SAM was not associated with age or time between scans. CONCLUSIONS AND CLINICAL IMPORTANCE: Similar proportions of cats gained or lost SAM. Cats with SAM at baseline had more evidence of disease progression than cats without SAM.
Keywords: cardiology; echocardiogram; echocardiograph; feline; obstructive cardiomyopathy